Event Stratigraphy in a Hadal Oceanic Trench: The Japan Trench as Sedimentary Archive Recording Recurrent Giant Subduction Zone Earthquakes and Their Role in Organic Carbon Export to the Deep Sea - Kioka, Arata; Schwestermann, Tobias; Moernaut, Jasper; Ikehara, Ken; Kanamatsu, Toshiya; Eglinton, Timothy I.; Strasser, Michael (Frontiers in Earth Science, 2019)
Hadal trenches are the deepest places on Earth and are important foci for natural carbon sequestration. Much of the sedimentary sequences that accumulate within hadal trenches have been linked to widespread slope sediment remobilisation events, triggered by subduction zone earthquakes. Therefore, hadal trench deposits may provide valuable insights into the hazards posed by large earthquakes and their implications for the carbon cycle. Despite this strong societal relevance, no studies to date have provided the necessary coverage to understand the spatial and temporal variations of earthquake-triggered deposition along a hadal trench axis. We address these issues by integrating high-resolution bathymetry and subbottom profiler data, and sediment cores acquired over the entire hadal trench axis of the Japan Trench. We identify around 40 isolated trench-fill basins along the trench axis of the Japan Trench that document 115 sediment remobilization event deposits. We map the spatio-temporal distribution of the acoustically-transparent event deposit bodies imaged in subbottom profiler data from the trench-fill basins. Using radiocarbon dating, slope failure deposits identified from subbotom profiles and sediment coring were shown to be co-eval with major historic earthquake (e.g., AD2011 Mw9.0–9.1 Tohoku-oki, AD1454 Mw≥8.4 Kyotoku, and AD869 Mw≥8.6 Jogan events). Furthermore, the lower part of the acoustically-imaged stratigraphic succession in isolated basins along the Japan Trench also documents several thick acoustically-transparent bodies that relate to older events. These identifications of event deposits allow quantitative constraints of along-strike variation of sediment volumes redistributed by episodic events along the entire trench axis, revealing that the total volumes of event deposits triggered by different historic large earthquakes are highly variable. We conclude that at least 7 Tg (1012 g) of organic carbon remobilized from surficial slope sediments is exported to the hadal axis of Japan Trench in the last 2,000 years by giant earthquakes. These findings highlight the significance of seismo-tectonic events for the long-term carbon cycle in hadal trenches and societal implications.